2011
DOI: 10.1021/la2036423
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Charge Balance in Organic Light-Emitting Diodes by Tuning Charge Injection Barriers with Mixed Monolayers

Abstract: Self-assembled monolayers (SAMs) of binary mixtures of 1-butylphosphonic acid and the trifluoromethyl-terminated analogue (4,4,4-trifluoro-1-butylphosphonic acid) were formed on ITO surfaces to tune the work function of ITO over a range of 5.0 to 5.75 eV by varying the mixing ratio of the two adsorbents. The mixed SAM-modified ITO surfaces were used as the anode in the fabrication of OLED devices with a configuration of ITO/SAM/HTL/Alq3/MX/Al, where HTL was the NPB or BPAPF hole-transporting layer and MX was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 63 publications
(42 reference statements)
0
29
0
1
Order By: Relevance
“…In this way, charge injection barriers can be controlled, with consequent effects on device performance . Multicomponent monolayers can offer a higher flexibility in tuning the work function if the molecular ratio is varied, and have been studied for this reason for some time . Most of these multi‐component layer studies use long, alkyl based molecules such as thiols, and the molecular monolayer is used as a buffer layer for deposition of a further organic layer atop.…”
Section: Binary Layers On Metal Surfacesmentioning
confidence: 99%
“…In this way, charge injection barriers can be controlled, with consequent effects on device performance . Multicomponent monolayers can offer a higher flexibility in tuning the work function if the molecular ratio is varied, and have been studied for this reason for some time . Most of these multi‐component layer studies use long, alkyl based molecules such as thiols, and the molecular monolayer is used as a buffer layer for deposition of a further organic layer atop.…”
Section: Binary Layers On Metal Surfacesmentioning
confidence: 99%
“…In order to improve the interface characteristics, the insertion of a buffer/injection layer between anode and hole transport layer (HTL) is one of the simple and effective methods to improve the device performances. An organic buffer layer, such as copper phthalocyanine (CuPc), 2 starburst amines (m-MTDATA), 3 poly (3,4-ethylene dioxythiophene) (PEDOT), 4 CHF 3 , 5 or self-assembled mono-layers (SAMs), 6 normally brings an energy-band alignment between the HTL and the anode, which lowers the energy barrier, reduces the turn-on voltage and increases the OLEDs lifetime. Inorganic insulator buffer layers, such as LiF, 7-9 Al 2 O 3 , 10 SiO 2 , 11 H f O x , 12 MoO 3 , 13 and WO 2.5 , 14 were also reported in literature, some of which showed higher current efficiency 9,11,12 and others showed higher power efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in the UFNP-device, the electron injects into the EML at $3.0 V, which is close to the voltage for the hole injection and achieves a better charge balance in HFSO for efficient radiative recombination. 19 The reduction of V t ($0.3 V) is higher than the energy discrepancy ($0.2 eV) of conduction band edges of UFNPs and NSNPs, probably with the enhancement of Auger-assisted energy up-conversion process suggested by Qian et al 20 Also, by reducing the leakage current observed in the NSNP-device, the UFNP-device can achieve higher L max (7300 cd m À2 ) and similar current efficiency (h c ) (1.13 cd A À1 , see Fig. 6(b)) compared to those (4300 cd m À2 and 1.12 cd A À1 ) of the counterpart with Ca/Al cathodes in our previous study.…”
Section: Resultsmentioning
confidence: 99%